Reconsidering The Battle of Hexham: A Lost Play by Barnabe Barnes? - Teramura, Misha (Early Theatre, 2023)
This note draws on new evidence from nineteenth-century auction catalogues to reconsider the question of whether Barnabe Barnes was the author of a lost play titled The Battle of Hexham.